Are the beneficial cardiovascular effects of simvastatin and metformin also associated with a hormone-dependent mechanism improving insulin sensitivity? - Bulcão,C. (2007)
In addition to lipid-lowering and cardiovascular protective actions, statins may have beneficial effects on insulin sensitivity. The objective of the present study was to evaluate the effect of simvastatin therapy on insulin resistance and on leptin, adiponectin, and C-reactive protein (CRP) levels, as compared to metformin, in overweight pre-diabetic subjects. Forty-one subjects with BMI >25 kg/m² and impaired fasting glucose or impaired glucose tolerance were randomized to take simvastatin, 20 mg/day (N = 20) or metformin, 1.7 g/day (N = 21) for 16 weeks. Blood samples for the determination of metabolic, hormonal, and inflammatory parameters were obtained at baseline and after each treatment. After metformin therapy, significant reductions in mean BMI and waist circumference were observed, and after simvastatin treatment LDL and triglyceride levels were significantly reduced. Insulin resistance determined by the homeostasis model assessment decreased only with metformin. Independently of the type of medication, a significant decrease in CRP levels was detected from baseline to the end of the study. CRP showed a mean reduction of 0.12 ± 0.04 mg/dL (P = 0.002) over time. No change in leptin or adiponectin levels was induced by any therapy. The data suggest that a low dose of simvastatin does not affect insulin resistance in overweight pre-diabetic subjects and has no effect on leptin or adiponectin levels. Further studies including a larger sample size, higher doses of statins, and a placebo control group are necessary to confirm the present data.